2016
DOI: 10.1038/srep31684
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical-Property Manipulation through Rapid Dendrite Growth and Undercooling in an Fe-based Multinary Alloy

Abstract: Rapid dendrite growth in single- or dual-phase multicomponent alloys can be manipulated to improve the mechanical properties of such metallic materials. Rapid growth of (αFe) dendrites was realized in an undercooled Fe-5Ni-5Mo-5Ge-5Co (wt.%) multinary alloy using the glass fluxing method. The relationship between rapid dendrite growth and the micro-/nano-mechanical properties of the alloy was investigated by analyzing the grain refinement and microstructural evolution resulting from the rapid dendrite growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 57 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…In additive manufacturing, two main solidification parameters are dendritic arm spacing and microsegregation. The distribution and the spacing of dendritic arms are related to mechanical properties, such as tensile strength and ultimate tensile strength [8][9][10]. Microsegregation, caused by non-equilibrium partition of solute in solid and liquid, affects the texture of dendrites.…”
Section: Introductionmentioning
confidence: 99%
“…In additive manufacturing, two main solidification parameters are dendritic arm spacing and microsegregation. The distribution and the spacing of dendritic arms are related to mechanical properties, such as tensile strength and ultimate tensile strength [8][9][10]. Microsegregation, caused by non-equilibrium partition of solute in solid and liquid, affects the texture of dendrites.…”
Section: Introductionmentioning
confidence: 99%
“…The improved properties were directly attributed to the nanostructured coating, which resulted in increased hardness and the formation of lubricating oxides. Ruan et al (2016) showed that decreasing dendrite diameter and secondary dendrite arm spacing both resulted in a microhardness increase, analogous to the Hall-Petch relationship. The presence of cellular dendritic structures in ESD processed materials have been reported for nickel based superalloys by Ebrahimnia et al (2014), which formed parallel to the ESD growth direction with submicron diameters.…”
Section: A C C E P T E D Mmentioning
confidence: 78%
“…Hence, it is essential to incorporate the solute interactions among all the components to understand the solidification behaviour of multi-component alloys. The measurement of undercooling using experiments can aid in the study of rapid solidification of multi-component systems [3]. The study of recalescence can be carried out by monitoring the thermal and spatial profiles during solidification in the undercooled melt [4].…”
Section: Introductionmentioning
confidence: 99%